Maize lodging resistance: Stalk architecture is a stronger predictor of stalk bending strength than chemical composition. (July 2022) - Robertson, Daniel J.; Brenton, Zachary W.; Kresovich, Stephen; Cook, Douglas D.
Abstract : The chemical composition of grain stalks has been extensively studied and has long been assumed to have a major influence on stalk lodging. However, much less attention has been given to the influence of stalk architecture (i.e. physical features of anatomy and morphology). We show in this study that stalk architecture is far more influential on stalk bending strength (a common measure of lodging resistance) than chemical composition. This insight was obtained through the novel combination of structural engineering principles and a plant-by-plant experimental design using two major grain species (maize and sorghum). Lodging resistance was quantified using stalk bending strength which provides plant-specific data while also removing dependence on weather events. Stalk anatomy and morphology as and chemical composition of the stalk were also measured for each specimen in this study. Statistical results indicate that (a) the quantification of stem architecture via engineering beam theory is four times more predictive of stalk bending strength than composition, and (b) stalk architecture and chemical composition are interrelated. These results explain why previous studies attempting to link chemistry and lodging have been inconsistent. Furthermore, these results indicate that future studies aimed at studying lodging must not overlook the dominant influence of stalk architecture. Highlights: Architectural, chemical composition, and bending strength measured for each specimen. Stalk architecture (anatomy/morphology) was highly predictive of bending strength. Chemical composition was weakly related to bending strength. Stalk architecture and chemistry are interrelated. Future studies should control for the powerful influence of stalk architecture.